Low-fat diet, and medium-fat diets containing coconut oil and soybean oil exert different metabolic effects in untrained and treadmill-trained mice - Mark Christian Manio; Shigenobu Matsumura; Kazuo Inoue (Taylor & Francis Group, 2018)
Background Diets containing fats of different proportions and types have been demonstrated to influence metabolism. These fats differ in long chain fatty acids (LCFAs) or medium chain fatty acids (MCFAs) content. In our laboratory using swimming as the training modality, MCFAs increased endurance attributed to increased activities of oxidative enzymes. How it affects whole-body metabolism remains unexplored. The present study investigated the metabolic, biochemical and genetic adaptations with treadmill running as the training modality. Methods C57BL/6N mice were divided into untrained and trained groups and provided with low-fat (10% kcal from soybean oil), coconut oil (10% kcal from soybean oil, 20% kcal from coconut oil) or soybean oil (30% kcal from soybean oil) diet. Training was performed on a treadmill for 30 days. After recovery, whole-body metabolism at rest and during exercise, endurance, substrate metabolism, mitochondrial enzyme activities, and gene expression of training-adaptive genes in the muscle and liver were measured. Results At rest, medium-fat diets decreased respiratory exchange ratio (RER) (p < 0.05). Training increased RER in all diet groups without affecting oxygen consumption (p < 0.05). During exercise, diets had no overt effects on metabolism while training decreased oxygen consumption indicating decreased energy expenditure (p < 0.05). Coconut oil without training improved endurance based on work (p < 0.05). Training improved all endurance parameters without overt effects of diet (p < 0.05). Moreover, training increased the activities of mitochondrial enzymes likely related to the increased expression of estrogen related receptor (ERR) α and ERRβ (p < 0.05). Coconut oil inhibited peroxisome proliferator-activated receptor (PPAR) β/δ activation and glycogen accumulation in the muscle but activated PPARα in the liver in the trained state (p < 0.05). Substrate utilization data suggested that coconut oil and/or resulting ketone bodies spared glycogen utilization in the trained muscle during exercise thereby preserving endurance. Conclusion Our data demonstrated the various roles of diet and fat types in training adaptation. Diets exerted different roles in PPAR activation and substrate handling in the context of endurance exercise training. However, the role of fat types in training adaptations is limited as training overwhelms and normalizes the effects of diet in the untrained state particularly on endurance performance, mitochondrial biogenesis, and ERR expression.